THE EFFECT OF DELAY IN OPERATION, QUALITY OF SERVICE AND COMPETENCE OF HEALTH CARE PERSONNEL ON SURGERY PATIENT SATISFACTION IN ONE OF THE PRIVATE HOSPITALS IN BANDUNG CITY - Irlan Karsa Gumilang; Haddan Dongoran; Rulia (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Increasing competition among hospitals demands continuous improvement in service quality, including surgical services. Surgical delays remain an operational issue that may affect operating room efficiency, healthcare staff workload, and patients' psychological conditions. in one of the private Hospital In Bandung City, internal data indicated that surgical delays exceeding 30 minutes still occurred in 18–22% of cases during a three-month observation period. In addition to timeliness, service quality and healthcare personnel competence are also important factors in shaping surgical patient satisfaction. This study aims to analyze the effect of surgical service delays, service quality, and healthcare personnel competence on surgical patient satisfaction in one of the private Hospital In Bandung City, both partially and simultaneously. The research employed a quantitative approach with a survey design. Data were collected through questionnaires distributed to patients who had undergone surgical procedures. Data analysis was conducted using multiple linear regression, supported by validity and reliability tests, classical assumption tests, t-tests, F-tests, and coefficient of determination analysis. The results indicate that surgical delays have a negative and significant effect on patient satisfaction. Conversely, service quality and healthcare personnel competence have positive and significant effects on patient satisfaction. Simultaneously, all three independent variables significantly influence patient satisfaction. In conclusion, improving surgical timeliness, service quality, and healthcare personnel competence is essential to improving surgical patient satisfaction in one of the private Hospital In Bandung City.